Pengaruh Minat, Kedisiplinan Dan Ketekunan Belajar Terhadap Motivasi Berprestasi Dan Dampaknya Pada Hasil Belajar Siswa Kelas 9 SMP N 5 Sukoharjo Tahun Pelajaran 2015/2016 - TAMARDIYAH, NURULIA DWIYANTI; , Prof. Dr. Sutama, M.Pd; , Dr. Sumardi, M.Si (2016)
The purpose of this research are: 1) To analyze and test the effect of interest on achievement motivation; 2) To analyze and test the effect on achievement motivation and discipline; 3) To analyze and test the effect of persistence on achievement motivation; 4) To analyze and test the effect of interest on learning outcomes; 5) To analyze and examine the influence of discipline on learning outcomes; 6) To analyze and test the effect of persistence on learning outcomes; 7) To analyze and test the effect of a significant motivation for learning outcomes; 8) To analyze and examine the effect of interest and discipline to achievement motivation; 9) To analyze and examine the effect of discipline and perseverance to achievement motivation; 10) To analyze and examine the effect of interest and perseverance to achievement motivation; 11) To analyze and examine the effect of interest, discipline and perseverance to achievement motivation; 12) To analyze and examine the effect of interest and discipline on learning outcomes; 13) To analyze and examine the effect of discipline and perseverance on learning outcomes; 14) To analyze and examine the effect of interest and perseverance towards learning outcomes; 15) To analyze and examine the effect of interest, discipline and perseverance on learning outcomes; 16) To analyze and examine the effect of interest, discipline and perseverance achievement motivation; 17) To analyze and examine the effect of interest, discipline and perseverance learning outcomes. This type of research is a kind of correlational study using a quantitative approach. In sampling the author uses simple random sampling technique with a number of students as the sample is 168 students. In the data collection methods of documentation and the researchers used the questionnaire method. The results showed that: 1) Interests has a positive and significant impact on achievement motivation; 2) The discipline has a positive effect but not significant achievement motivation; 3) Perseverance has a positive effect but not significant achievement motivation; 4) Interest have a positive effect but not significant on learning outcomes; 5) The discipline has a positive and significant impact on learning outcomes; 6) Perseverance has a positive and significant impact on learning outcomes; 7) Achievement motivation has a positive and significant impact on learning outcomes; 8) Interest and discipline have influence simultaneously and significantly to the achievement motivation; 9) Discipline and perseverance have no effect simultaneous and significant achievement motivation; 10) Interests and perseverance have influence simultaneously and significantly to the achievement motivation; 11) Interest, discipline and perseverance have influence simultaneously and significantly to the achievement motivation have influence simultaneously and significantly to the achievement motivation; 12) Interest and discipline have simultaneous and significant effect on learning outcomes; 13) Discipline and perseverance have a simultaneous and significant effect on learning outcomes; 14) Interest and perseverance have a simultaneous and significant effect on learning outcomes; 15) Interest, discipline and perseverance have a simultaneous and significant effect on learning outcomes; 16) Interest, discipline and perseverance indirect effect on achievement motivation; 17) Interest, discipline and perseverance indirect effect on learning outcomes. Keywords: interest, discipline, perseverance learning, achievement motivation, learning outcomes, SMP N 5 Sukoharjo